BIOTERRORISM: THE DEVELOPMENT AND ITS REGULATIONS ACCORDING TO THE INTERNATIONAL LAW - Yaksa Elyasa (Lampung Journal of International Law, 2021)
The biological weapon used as a terrorism facility (bioterrorism) could endanger the lives of mankind. Besides its purpose of mass destruction, this weapon has been banned from being used towards the human. Bioterrorism threat at least had occurred in more than 30 countries across the globe. In the 14th century, bioterror incidents recorded in black death plagues in Europe caused more than 50 million deaths and vanished more than 60% of its population back then. Because of the bioweapon impacts, there are concerns if this weapon is under irresponsible parties such as the group of terrorists. Several regulations on the prohibition of biological weapons have been made, such as the Production and Stockpiling of Bacteriological [Biological] and Toxin Weapons and Their Destruction 1972 (Biological Weapon Convention 1972). However, it seems that they have not solved using biological weapons as a means of terrorism. The purpose of this paper is to find out how international law arrangements regarding bioterrorism. This research used normative legal research with secondary data sources and literature study techniques.